1986
DOI: 10.1111/j.1751-0813.1986.tb02923.x
|View full text |Cite
|
Sign up to set email alerts
|

Left abomasal displacement and ulceration in an eight‐week‐old calf

Abstract: Left displacement of the abomasum was diagnosed radiographically in an 8-week-old female Friesian calf. At surgery, a 4 cm ulcer was repaired and an abomasopexy performed during closure of the abdomen. Recovery from surgery was slow, and regurgitation of rumen contents occurred. Despite medical treatment, the calf died 4 days later. Left abomasal displacement is a well documented disease of dairy cattle (Robertson 1968; Coppock 1974; Martin et al 1978a; Poulsen 1976), but in young calves the condition is rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 1 publication
0
10
0
1
Order By: Relevance
“…A ocorrência de deslocamento de abomaso em bezerros ainda é pouco documentada na literatura (Mueller et al, 1999). Apesar disso, DAE foi relatado em bezerros com mais de uma semana (Fierheller, 2002), oito semanas (Hawkins et al, 1986;Mueller et al, 1999), duas semanas a três meses (Oman et al, 2016) e associado a doenças respiratórias (Katsoulos et al, 2016). Já os relatos de DAD são escassos, sendo relatado em bezerros com menos de um ano de idade (Dezfouli et al, 2016) e associado à úlcera abomasal em uma bezerra com oito semanas (Altan et al, 2012).…”
Section: Discussionunclassified
“…A ocorrência de deslocamento de abomaso em bezerros ainda é pouco documentada na literatura (Mueller et al, 1999). Apesar disso, DAE foi relatado em bezerros com mais de uma semana (Fierheller, 2002), oito semanas (Hawkins et al, 1986;Mueller et al, 1999), duas semanas a três meses (Oman et al, 2016) e associado a doenças respiratórias (Katsoulos et al, 2016). Já os relatos de DAD são escassos, sendo relatado em bezerros com menos de um ano de idade (Dezfouli et al, 2016) e associado à úlcera abomasal em uma bezerra com oito semanas (Altan et al, 2012).…”
Section: Discussionunclassified
“…All panels: 1 = rumen dorsal sac, 2 = rumen ventral sac, 3 = abomasum, 4 = left hepatic lobe, 5 = intestine. however, some clinical cases have been reported, for example, in two 4-wk-old calves (Mueller et al, 1999), in a 7-wk-old calf (King, 1979), and in a 8-wk-old calf (Hawkins et al, 1986).…”
Section: The Stomach In Situmentioning
confidence: 99%
“…In previous studies, the form of the abomasum in cases of DA was based on frozen autopsy findings [ 12 ], radiographic images [ 7 , 17 ], ultrasonography [ 2 , 3 ] and laparoscopy [ 15 ]. In addition, it was reported that DA occurred in cows with insufficient feed intake and a decreased rumen volume [ 16 ].…”
mentioning
confidence: 99%